Rekacipta Website Bilingual Desa Mangga II sebagai Media Publikasi Kegiatan Desa dan Promosi Potensi Desa - Fau, Alwin; Hasibuan, Nelly Astuti; Putri Ramadhani, (TAAWUN, 2022)
Manga Dua Village is one of the villages located in Tanjun Beringin District, Serdan Bedagai Regency, North Sumatra. Mangga Dua Village has great potential in agriculture, especially in rice fields. The agricultural potential of Mangga Dua village is very good, but it has never been promoted through public media that can be accessed by the wider community. For this reason, Mandua Village needs media to promote and promote the village's potential. The village website has benefits that are felt by many stakeholders, both village officials, village communities, and other stakeholders who need information about the village. Village websites can be used to promote village activities in the media and promote village potential. Mangga II village website design aims to assist the village in publicizing its activities and promoting the potential of the village.